A Comprehensive Risk Evaluation: A Case Study of Super Madi Hydropower Project - Ojha, Rabindra Nath; Baral, Sanjay; Mishra, Binay Kumar (Journal of Engineering Issues and Solutions, 2025)
Hydropower projects are a great source of clean energy, but they come with many risks that can affect their success. Risk is anything that can delay a project, raise costs, or lower quality. It is important to correct and manage risks early, before the project starts. The study aims to uncover conceivable risks inherent in hydropower projects. The fundamental goal of this study is to determine the likelihood of risk occurrences in hydropower projects, from conceptualization to operationalization. A quantitative research approach was employed, utilizing structured questionnaires distributed to key stakeholders involved in the Super Madi Hydroelectric Project (SMHP), including clients, contractors, and consultants. A total of 48 questionnaires were distributed, with 47 responses received. The questionnaire comprised 34 questions across seven major risk categories, and risk prioritization was conducted using the Relative Importance Index (RII). The reliability of the data was confirmed with Cronbach’s alpha (α = 0.786), ensuring internal consistency. The results identified natural calamities as the most significant physical risk, followed by geological and groundwater subsurface conditions. Additionally, labor and material availability, inflation, regulatory changes, and environmental impacts were identified as critical risk factors. This kind of information can help future hydropower projects plan better, avoid common problems, and stay on track. Managing these risks well can lead to safer, more efficient, and more sustainable energy projects.